Effect of Pseudomonas fluorescens formulations on decay and quality of mango (Mangifera indica) fruits during storage - BARMAN, KALYAN; ASREY, RAM; SINGH, DINESH; PATEL, V B; SHARMA, SWATI (The Indian Journal of Agricultural Sciences, 2017)
Anthracnose and stem-end rot caused by Colletotrichum gleosporioides and Botryodiplodia theobromae, respectively are the most important postharvest diseases of mango (Mangifera indica L.) causing huge economic losses. In this study, biocontrol efficacy of Pseudomonas fluorescens was evaluated against anthracnose and stemend rot of naturally infected mango fruits during their postharvest storage. Physiologically mature mango fruits were treated with P. fluorescens formulations (107 cfu/ml and 108 cfu/ml) by dipping them for 5 min. Following treatment,fruits were air-dried and stored at ambient condition (30º ± 2ºC) for 12 days. Among the treatments, P. fluorescens 108 cfu/ml showed significant reduction (5.92%) in decay loss of mango fruit compared to control (24.52%). Respiration and ethylene evolution rates were also brought down by P. fluorescens treatments. Loss of firmness, total phenolics content and titratable acidity were also found lower in P. fluorescens treated fruits. No significant differences in a* and b* values of fruit colour was recorded between control and treated fruits while, the L* value was lowest in control fruits. The fruits treated with P. fluorescens @ 108 cfu/ml maintained highest total carotenoids and total soluble solidscontent than other treatments. Therefore, P. fluorescens @ 108 cfu/ml treatment may be used as a potential biocontrol agent in reducing anthracnose and stem-end rot, and maintaining desirable fruit quality attributes of mango during postharvest storage.